Pengaruh Employee Engagement terhadap Kinerja Karyawan pada Perusahaan SKK Migas: - Aldira, Zahwa Namira; Andriana, Isni; Farla, Wita; Santati, Parama (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of employee engagement on employee performance at SKK Migas companies (KKKS Energy Equity Epic Sengkang). The type of research used is quantitative descriptive research. Data collection methods in this study using a questionnaire. The sampling technique used is saturated sampling technique with a total sample of 58 people. The analysis technique used is simple linear regression analysis. Based on the results of the study it can be concluded that employee engagement has a significant effect on employee performance at SKK Migas companies (KKKS Energy Equity Epic Sengkang). Keywords: Employee engagement; employee performance